Investigaciones sobre videojuegos masivos en línea: hacia un estado de la cuestión - Orozco Gálvez, Ricardo (Universidad de San Buenaventura - Cali, 2017)
The following document presents a state of the art of research in the field of social and human sciences and education around massive video games online, as a central cultural practice in the contemporary generations. To meet this objective, an analysis bibliographic was led into three conceptual categories anchor: the psychological and anthropological definition of the play; the experience of the players, with an emphasis on the subjective processes involved in it: the recognition and prestige; and roles in the video games. As a fundamental result in the revised investigations, we found that most of studies have given an a priori ontological status to the videogame as a technological artifact, and have ignored the singularity of subjective processes produced by the players, which are who really give life to this cultural practice.